Examination Questions and Answers in Basic Anatomy and Physiology 2400 Multiple Choice Questions - Caon, Martin (Springer International Publishing, 2018)
This second edition provides 2400 multiple choice questions on human anatomy and physiology, and some physical science, separated into 40 categories. The answer to each question is accompanied by an explanation. Each category has an introduction to set the scene for the questions to come. However, not all possible information is provided within these Introductions, so an Anatomy and Physiology textbook is an indispensable aid to understanding the answers. The questions have been used in end-of-semester examinations for undergraduate anatomy and physiology courses and as such reflect the focus of these particular courses and are pitched at this level to challenge students that are beginning their training in anatomy and physiology. The question and answer combinations are intended for use by teachers, to select questions for their next examinations, and by students, when studying for an upcoming test. Students enrolled in the courses for which these questions were written include nursing, midwifery, paramedic, physiotherapy, occupational therapy, nutrition and dietetics, health sciences, exercise science, and students taking an anatomy and physiology course as an elective.